Historical dictionary of Brexit - Laursen, Finn (Historical dictionaries of international organizations series., 2021)
"Historical Dictionary of Brexit contains a chronology, an introduction, an extensive bibliography, and more than 300 cross-referenced entries on the terms, people, and events that shaped Brexit"--